Molecular dynamics simulation research on the interaction between plasma and living organisms: A comprehensive review - Li, Yan; Tan, Shihao; Liu, Dawei; Zhang, Yuantao (Plasma processes and polymers, 2024)
In recent years, plasma biomedicine has developed into a new interdisciplinary subject. The interaction between plasma and organisms involves three aspects: “gas–liquid–living organisms.” Molecular dynamics (MD) simulation can simulate the interaction process between plasma and biological tissue with high temporal and spatial resolution. This article reviews the research on plasma biomedicine based on MD simulation and systematically summarizes the progress of MD simulation research on the interaction between plasma and water layer, cell membrane, intracellular substances, extracellular environment, and viruses. These simulations offer a unique opportunity to gain insights into the microscopic mechanisms of these interactions. This article also further looks forward to the opportunities and challenges of MD simulation research. The progress in plasma biomedicine research based on MD simulation mainly covers four aspects: interactions of plasma with water, cells, the extracellular environment, and viruses.